Cryotechnologies in animal breeding: EU experience and opportunities for Ukraine ̉s integration - Bogdaniuk, Anastasiia; Otter, Tom; Petrushko, Maryna (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):236